Development of To-Do List and Monetary Management System - Diana anak Ringgau; Chen Wong Keong; Bong Siaw Wee (International ABEC, 2021)
Currently, most of the available “To-Do List” Applications on Android or iOS are just consisted of a “To-Do list” and integrated with an electronic calendar. These applications are just suitable for individual use for keeping alert daily “To Do List” and its functionality is limited to update the status of each task. The other limitation of these applications is the “To-Do List” could not be easily shared and updated if involved other group members. Therefore, a new “Group To- Do List” plus Monetary Management System application was proposed. The proposed application can be shared and updated by group members of interest in communicating and monitoring “To Do List’ and fund management. This application was developed based on Rapid Application Development Method (RAD) by understanding the natural practices of task management and quantities of tasks taken on by team members. Therefore, this app can be expanded and customized to integrate other attractive functions based on user requests. This new application is suitable for family members, project group members, or even individuals from all walks of life who are interested in managing a total integrated “To-Do List” plus finance management system. Some of the important features of this application are its ability to identify tasks that need to be completed on daily basis with indications of which tasks need financial support, and which tasks could generate income. An interactive table and bar charts have summarized all of these tasks with details of expenditure/income and are integrated into an electronic calendar. The status of these tasks could be updated by group members with ease on individual tablets/handphones/computers/laptops. This application can be expanded/customized to integrate other attractive functions based on user requests.